Prdx6 regulates in vivo myeloid cell development via redox control during Xenopus embryogenesis - Minjoo Kim; Hyun-Kyung Lee; Hongchan Lee; Hyun-Shik Lee (Animal Cells and Systems)
Peroxiredoxin6 (Prdx6) is a bifunctional antioxidant enzyme with both peroxidase and phospholipase A₂ activities. Although its molecular roles are well established, the developmental role of Prdx6 remains poorly understood. To address this gap in the literature, this study aimed to examine the in vivo function of Prdx6 in primitive myelopoiesis using Xenopus laevis embryos. We found that prdx6 is specifically expressed in myeloid progenitors originating from the anterior ventral blood island during early embryogenesis. Knockdown of prdx6 significantly reduced the number of myeloid cells, without affecting their migration ability. Embryos depleted of prdx6 exhibited elevated levels of reactive oxygen species (ROS) and decreased cellular proliferation. Co-injection of morpholino (MO)-resistant prdx6 mRNA or treatment with N-acetylcysteine (NAC) successfully restored both ROS levels and myeloid cell numbers, suggesting that Prdx6 supports primitive myeloid cell development by maintaining redox homeostasis. These findings reveal a novel role of Prdx6 in ROS-dependent proliferation of myeloid progenitors during early vertebrate development.